Identification and Differentiation of Mycobacterium Avium Subspecies Paratuberculosis Isolates Using and pAM-3 as a DNA Probe - Karim S A Al-Ajeeli; Amer Al-Azawy; Suri Arshad; Sharifah S.H (Diyala Journal of Medicine, 2019)
Background: Mycobacteriu avium subsp.paratuberculosis (MAP) is the causative agent of Johne’s disease. It is a very slow growing bacterium on synthetic medium. The use of conventional methods for diagnosis is time consuming and not accurate.